Georges Perec's Geographies Material, Performative and Textual Spaces (University College London, 2019)
Georges Perec, novelist, filmmaker and essayist, was one of the most inventive and original writers of the twentieth century. A fascinating aspect of his work is its intrinsically geographical nature. With major projects on space and place, Perec's writing speaks to a variety of geographical, urban and architectural concerns, both in a substantive way, including a focus on cities, streets, homes and apartments, and in a methodological way, experimenting with methods of urban exploration and observation, classification, enumeration and taxonomy. Georges Perec's Geographies is the first book to offer a rounded picture of Perec's geographical interests. Divided into two parts, Part I, Perec's Geographies, explores the geographies within Perec's work in film, literature and radio, from descriptions of streets to the spaces of his texts, while Part II, Perecquian Geographies, explores geographies in a range of material and metaphorical forms, including photographic essays, soundscapes, theatre, dance and writing, created by those directly inspired by Perec. Georges Perec's Geographies extends the body of Perec criticism beyond Literary and French Studies to disciplines including Geography, Urban Studies, Planning and Architecture to offer a complete and systematic examination of Georges Perec's geographies. The diversity of readings and approaches will be of interest not only to Perec readers and fans but to students and researchers across these subjects.